Chapter Il sogno della scuola umanistica di Claudio Magris - Encarna, Esteban Bernabé (Biblioteca di Studi di Filologia Moderna, 2021)
The current essay presents Claudio Magris' key ideas on a pedagogical model for present-day society. Arguably, though perhaps inadvertently, Magris developed a particularly useful concept of humanist school for today's society across his prolific career. His pedagogical ideas appear in his articles, essays and even his fiction, over the years. This article is focused on the main issues that make up Claudio Magris' concept of humanist school.